2004
DOI: 10.1529/biophysj.104.042895
|View full text |Cite
|
Sign up to set email alerts
|

DNA Release from Lipoplexes by Anionic Lipids: Correlation with Lipid Mesomorphism, Interfacial Curvature, and Membrane Fusion

Abstract: DNA release from lipoplexes is an essential step during lipofection and is probably a result of charge neutralization by cellular anionic lipids. As a model system to test this possibility, fluorescence resonance energy transfer between DNA and lipid covalently labeled with Cy3 and BODIPY, respectively, was used to monitor the release of DNA from lipid surfaces induced by anionic liposomes. The separation of DNA from lipid measured this way was considerably slower and less complete than that estimated with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 52 publications
(76 reference statements)
8
100
2
Order By: Relevance
“…156 A perspective for future research is to enrich the physical understanding of DNA release from sub-mm sized DNA-CL complexes and their translocation into cell cytoplasm across a negatively charged cellular membrane. 136,158 Both processes are necessary for efficient gene delivery, with the transfection efficiency 159 of DNA-CL complexes still remaining low as compared to viral-based gene carriers. 136 It is known for instance that spermine 3+ and spermidine 4+ not only condense DNAs in DNA-CL complexes, but can also trigger DNA release from the complexes via DNA condensation into dense aggregates in solution.…”
Section: Dna Complexes With Lipid Membranesmentioning
confidence: 99%
“…156 A perspective for future research is to enrich the physical understanding of DNA release from sub-mm sized DNA-CL complexes and their translocation into cell cytoplasm across a negatively charged cellular membrane. 136,158 Both processes are necessary for efficient gene delivery, with the transfection efficiency 159 of DNA-CL complexes still remaining low as compared to viral-based gene carriers. 136 It is known for instance that spermine 3+ and spermidine 4+ not only condense DNAs in DNA-CL complexes, but can also trigger DNA release from the complexes via DNA condensation into dense aggregates in solution.…”
Section: Dna Complexes With Lipid Membranesmentioning
confidence: 99%
“…By exclusion of alternatives, cationic liposomes have emerged as morphology (lipoplex size, charge ratio (+/-), fluidity and structure) for optimal transfection conditions. In this way, the behaviour of the lipofection reagent (resistance to extracellular components, cytotoxicity) in vitro and in vivo is more predictable [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the depot effect at the SOI, the formulations were able to cause antigen retention between the range of 59 and 79% of the antigen dose recovered one day p.i. The key step in lipid-mediated DNA delivery may be the structural changes of lipid carriers resulting in DNA release (Tarahovsky et al, 2004;Koynova et al, 2006;Hoekstra et al, 2007). In recent times, it was shown that multicomponent lipoplexes are superior in transfection with respect to the binary ones usually employed for gene delivery (Caracciolo et al, 2005a;2005b;.…”
Section: Dc-cholmentioning
confidence: 99%